Delayed Diagnosis of Proteinase 3- Anti-Neutrophil Cytoplasmic Antibody Associated Vasculitis, A Case Report and Review of Literature: Delayed Diagnosis of Proteinase 3- Anti-neutrophil cytoplasmic antibody Associated Vasculitis. - Sampathkumar, Gopika; Yu, Yamin; Wen, Ailing; Zhang, Yide (Journal of Pediatric Nephrology, 2021)
Anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis is a type of systemic autoimmune disease with blood vessels swelling and inflammation. Wegener's Granulomatosis (WG) is closely associated with antineutrophil cytoplasmic autoantibodies, particularly those directed to proteinase 3 (PR3). An 18-year-old boy with granulomatosis with polyangiitis (GPA) who was diagnosed 6 months back with scleritis and sinusitis at the onset of the disease. During his initial visits to Ear Nose Throat and ophthalmology departments lab tests was not performed on time due to lack of typical symptoms of kidney involvement. Half a year later, lab tests showed PR3-ANCA (Proteinase 3) positive and advanced renal dysfunction, and was finally diagnosed as sclerotic renal failure with fibrotic crescents based on renal biopsy. Scleritis may be the earliest manifestation in systemic vasculitis and is sometimes hard to diagnose at the onset. Delayed diagnosis and treatment will lead to irreversible renal dysfunction.